A 12‐Week, Open Label, Multi‐Center Study to Evaluate the Clinical Efficacy and Safety of Silodosin on Voiding Dysfunction in Patients with Neurogenic Bladder. Issue 1 (19th November 2013) - MOON, Kyung Hyun; PARK, Choal‐Hee; JUNG, Hee‐Chang; OH, Tae‐Hee; KIM, Jae‐Soo; KIM, Duk‐Yoon
<x xml:space="preserve">Abstract</x> Objectives The purpose of this study is to evaluate clinical effect and safety of α1A‐adrenoceptor blocker, silodosin, in patients with voiding dysfunction caused by neurogenic bladder. Methods From April 2011 to January 2012, patients who were diagnosed as potential voiding dysfunction associated with neurogenic bladder, aged ≥ 20 years were enrolled. Silodosin (8 mg/day) was administered once daily in the morning with food. The efficacy was assessed at the baseline and after 12 weeks of the treatment having following parameters of international prostate symptom score and other measures including the maximum flow rate and the postvoid residual urine volume. Results A total of 97 patients were screened and 95 were enrolled. Of these 95 patients, 82 patients were completed and included in analysis. After 12‐weeks of treatment, mean total international prostate symptom score decreased significantly from 22.23 ± 6.80 to 14.98 ± 9.48 (P = 0.0002). Voiding symptoms and storage symptoms were also improved by decreasing in international prostate symptom score‐QoL from 4.62 ± 0.92 to 3.48 ± 1.63 (P < 0.0001). Maximum flow rate increased significantly from 10.72 ± 2.66 to 15.14 ± 6.63 (P < 0.0001). The main adverse event was ejaculation disorder. No serious adverse events related to silodosin were noted. Conclusions This study indicates that silodosin was significantly effective, well tolerated and safe in patients who have voiding dysfunction associated with neurogenic bladder.